Pengaruh Penerimaan Pajak Parkir, Pajak Penerangan Jalan, Dan Pajak Hotel Terhadap Pendapatan Asli Daerah Kota Blitar - Lis Lestari Sukartiningsih; Aan Al Basyarah (Universitas Katolik Widya Karya Malang, 2021)
This study aims to analyze the effect of parking taxes, street lighting taxes and hotel taxes on the local revenue of Blitar City in 2016-2020. The primary data used in this study was obtained from the BPKAD office in Blitar City, including the realization of parking tax revenue, street lighting tax, hotel tax and regional income for 2016-2020. The type of research used is explanatory research, using multiple linear analysis tools and testing the hypothesis using the t test and F test. The results of the quantitative descriptive analysis show that parking taxes, street lighting taxes and hotel taxes have a simultaneous and significant effect on real income. area. Partially, parking tax, street lighting tax and hotel tax have an effect on local revenue, but parking tax has a negative effect on local revenue, and street lighting tax has no significant effect on local revenue of Blitar City. In the results of the dominant test analysis, hotel tax is the most dominant variable in the local revenue of the city of Blitar.